(untitled) (Innovative professional education, 2025)
In the article, the author highlights the current state of professional training of future green construction specialists. Provides the results of the analysis of the global trend «green construction» in the Google Trends search engine, the definition of «green construction», the Ukrainian legislative framework in the areas of green construction and professional (vocational) education. Analyzes the National Classifier of Ukraine «Classifier of Professions» and the Unified State Electronic Database on Education for the search query «green construction».